Question
upstudy study bank question image url

What is the equation of the line perpendicular to \( y=\frac{-1}{5} x-25 \) that passes through the point \( (-2,-4) \) ?

Ask by Mcfarlane Reyes. in the United States
Feb 02,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The equation of the perpendicular line is \( y = 5x + 6 \).

Solution

To find the equation of the line perpendicular to \( y = \frac{-1}{5}x - 25 \) that passes through the point \( (-2, -4) \), follow these steps: 1. **Determine the slope of the given line:** The equation \( y = \frac{-1}{5}x - 25 \) is in the slope-intercept form \( y = mx + b \), where \( m \) is the slope. \[ m_1 = -\frac{1}{5} \] 2. **Find the slope of the perpendicular line:** The slope of a line perpendicular to another is the negative reciprocal of the original slope. \[ m_2 = -\frac{1}{m_1} = -\frac{1}{-\frac{1}{5}} = 5 \] 3. **Use the point-slope form to write the equation of the perpendicular line:** The point-slope form is: \[ y - y_1 = m(x - x_1) \] Plugging in the slope \( m = 5 \) and the point \( (-2, -4) \): \[ y - (-4) = 5(x - (-2)) \\ y + 4 = 5(x + 2) \] 4. **Simplify to slope-intercept form:** \[ y + 4 = 5x + 10 \\ y = 5x + 10 - 4 \\ y = 5x + 6 \] **Final Equation:** \[ \boxed{y = 5x + 6} \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

To find the equation of the line perpendicular to \( y = \frac{-1}{5} x - 25 \), we first need to determine the slope of the given line. The slope is \( \frac{-1}{5} \). The slope of a line perpendicular to this will be the negative reciprocal, which is \( 5 \). Now, using the point-slope form of the equation of a line, which is given by \( y - y_1 = m(x - x_1) \), where \( m \) is the slope and \( (x_1, y_1) \) is the point the line passes through, we can plug in our values. Here, \( m = 5 \) and the point is \( (-2, -4) \). Substituting in the values, we have: \[ y - (-4) = 5(x - (-2)) \] This simplifies to: \[ y + 4 = 5(x + 2) \] Now distributing the \( 5 \): \[ y + 4 = 5x + 10 \] Next, we solve for \( y \): \[ y = 5x + 10 - 4 \] This gives us the final equation of the line: \[ y = 5x + 6 \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy